2010
DOI: 10.1097/mao.0b013e3181ec1d61
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging at 1.5 T After Cochlear Implantation

Abstract: Patients can safely undergo 1.5 T MRI after CI if the device is tightly bound before scanning. Magnet displacement was not observed, and we think the risk to be minimal compared with the risk and inconvenience of removing the magnet before the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 16 publications
5
96
0
3
Order By: Relevance
“…The operation can be performed with a small incision in the skin under local anesthesia. Explantation of the internal magnet and reimplantation after MRI were to be performed on the same day to keep the risk of infection as low as pos- sible [15,16]. In the present collective, this method was performed in 8 cases among 2027 CI operations in the period between 2004 and 2009 and resulted in 34.8 % of all magnet revision surgeries.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The operation can be performed with a small incision in the skin under local anesthesia. Explantation of the internal magnet and reimplantation after MRI were to be performed on the same day to keep the risk of infection as low as pos- sible [15,16]. In the present collective, this method was performed in 8 cases among 2027 CI operations in the period between 2004 and 2009 and resulted in 34.8 % of all magnet revision surgeries.…”
mentioning
confidence: 92%
“…In relation to special implant types, multiple in vitro and in vivo studies were able to show that MRI examinations can be performed safely if the magnet remains in the silicone pocket. However, special implant-dependent precautions must be taken: For example, no field strengths above 1.5T; use of a compression head bandage; prior comprehensive patient counseling [7,15,16,18]. In the case of an indicated MRI examination, this bandage technique was used without prior explantation of the internal magnet starting in 2009 at our clinic, provided that the particular CI system was approved.…”
mentioning
confidence: 99%
“…On the one hand, there are large artifacts on the MRI when the magnet is not removed and only a bandage is used during the imaging studies [3] . Crane et al [3] found that the CI generally produced an artifact on brain MRIs, with a mean maximal anterior-posterior dimension of 6.6 cm and a lateral dimension of 4.8 cm around the site of the device. They reported that the contralateral internal auditory canal was visualized in all of their 16 patients, and that the ipsilateral internal auditory canal was at least party visible in all but 1 patient.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that surgical removal of the internal magnet before scanning with the 1.5-Tesla MRI may not be necessary if a compression dressing is applied. However, there are no exact data on the number and outcome of CI recipients who had already undergone MRI studies with and without removing the CI internal magnet, so the controversy over the necessity of its removal remains unresolved [3,4] . This is the first paper describing the surgical procedure of magnet removal with subsequent reinsertion in a CI recipient who underwent an MRI.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] There are several other implanted devices that are more controversial, including vagal nerve stimulators 29 and cochlear implants. 30 The most important intervention the anesthesiologist can make is to have conversations with the institutional MRI safety officer prior to scheduling patients with questionable implantable devices in an ioMRI suite.…”
Section: Patient Concernsmentioning
confidence: 99%